2022
DOI: 10.52547/jrdms.7.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Techniques and Materials for Treatment of Bone Loss Due to Periodontitis: A Review

Abstract: Background and Aim:The first purpose of treatment of periodontal disease and bone loss is to regenerate the lost structures and preserve the sound residual tissues. Different techniques and materials are utilized for alveolar bone loss treatment. This review summarizes the techniques and materials utilized for treatment of alveolar bone loss due to periodontitis. Materials and Methods: A search was performed in PubMed, Cochrane Library, and Google Scholar databases from 1990 to 2021. Totally, 133 studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…These results are in consistence with the previous findings. As per another study that was carried out to study the efficacy of these crystal of calcium phosphate in the treatment of periodontal defects it was found that there was no significant difference found between the control and the test group 19 . After the surgery gingival recession was observed in both the groups, and the comparison shows that non-significant interaction was found between them.…”
Section: Discussionmentioning
confidence: 91%
“…These results are in consistence with the previous findings. As per another study that was carried out to study the efficacy of these crystal of calcium phosphate in the treatment of periodontal defects it was found that there was no significant difference found between the control and the test group 19 . After the surgery gingival recession was observed in both the groups, and the comparison shows that non-significant interaction was found between them.…”
Section: Discussionmentioning
confidence: 91%